Hexokinase 2‐dependent hyperglycolysis driving microglial activation contributes to ischemic brain injury. Issue 2 (9th January 2018) - Li, Yuan; Lu, Bingzheng; Sheng, Longxiang; Zhu, Zhu; Sun, Hongjiaqi; Zhou, Yuwei; Yang, Yang; Xue, Dongdong; Chen, Wenli; Tian, Xuyan; Du, Yun; Yan, Min; et al.
Abstract : Hyperglycolysis, observed within the penumbra zone during brain ischemia, was shown to be detrimental for tissue survival in clinical and experimental settings. Here, we identify a hexokinase 2 (HK2)‐dependent pathway for microglial inflammatory activation in ischemic damage. The induced key glycolytic enzyme HK2 activates the transcription of cytokine interleukin (IL)‐1β through acetyl‐coenzyme A accumulation and histone acetylation in hypoxic environment. The key role of HK2 in neuroinflammation provides novel insights for hyperglycolysis‐mediated brain injury, suggesting the possible benefits of selectively targeting HK2 for acute ischemic stroke. Abstract: Hyperglycolysis, observed within the penumbra zone during brain ischemia, was shown to be detrimental for tissue survival because of lactate accumulation and reactive oxygen species overproduction in clinical and experimental settings. Recently, mounting evidence suggests that glycolytic reprogramming and induced metabolic enzymes can fuel the activation of peripheral immune cells. However, the possible roles and details regarding hyperglycolysis in neuroinflammation during ischemia are relatively poorly understood. Here, we investigated whether overactivated glycolysis could activate microglia and identified the crucial regulators of neuroinflammatory responses in vitro and in vivo . Using BV 2 and primary microglial cultures, we found hyperglycolysis and induction of the key glycolytic enzyme hexokinase 2 (HK2) were essential for microglia‐mediated neuroinflammation under hypoxia. Mechanistically, HK2 up‐regulation led to accumulated acetyl‐coenzyme A, which accounted for the subsequent histone acetylation and transcriptional activation of interleukin (IL)‐1β. The inhibition and selective knockdown of HK2 in vivo significantly protected against ischemic brain injury by suppressing microglial activation and IL‐1β production in male Sprague–Dawley rats subjected to transient middle cerebral artery occlusion (MCAo) surgery. We provide novel insights for HK2 specifically serving as a neuroinflammatory determinant, thus explaining the neurotoxic effect of hyperglycolysis and indicating the possibility of selectively targeting HK2 as a therapeutic strategy in acute ischemic stroke.